Self Assembly–Assisted Additive Manufacturing: Direct Ink Write 3D Printing of Epoxy–Amine Thermosets. Issue 3 (4th December 2018) - Manning, Kylie B.; Wyatt, Nicholas; Hughes, Lindsey; Cook, Adam; Giron, Nicholas H.; Martinez, Estevan; Campbell, Christopher G.; Celina, Mathias C.
Abstract: The use of self‐assembling, pre‐polymer materials in 3D printing is rare, due to difficulties of facilitating printing with low molecular weight species and preserving their reactivity and/or functions on the macroscale. Akin to 3D printing of small molecules, examples of extrusion‐based printing of pre‐polymer thermosets are uncommon, arising from their limited rheological tuneability and slow reactions kinetics. The direct ink write (DIW) 3D printing of a two‐part resin, Epon 828 and Jeffamine D230, using a self‐assembly approach is reported. Through the addition of self‐assembling, ureidopyrimidinone‐modified Jeffamine D230 and nanoclay filler, suitable viscoelastic properties are obtained, enabling 3D printing of the epoxy–amine pre‐polymer resin. A significant increase in viscosity is observed, with an infinite shear rate viscosity of approximately two orders of magnitude higher than control resins, in addition to, an increase in yield strength and thixotropic behavior. Printing of simple geometries is demonstrated with parts showing excellent interlayer adhesion, unachievable using control resins. Abstract : The material scope of 3D printing, using direct ink write technologies, is still very limited. This is mainly due to the precise rheological profiles and viscoelastic properties required of inks. A new approach for modifying the rheology of a previously unprintable resin composed of Epon 828 and Jeffamine D230 through the incorporation of supramolecular, ureidopyrimidinone crosslinks is reported.